No evidence of increased risk of thyroid dysfunction in well treated people living with HIV. (24th September 2018) - Harsløf, Mads; Knudsen, Andreas D.; Benfield, Thomas; Nordestgaard, Børge G.; Feldt-Rasmussen, Ulla; Nielsen, Susanne D.
Abstract : Objectives: Possible effects of HIV on thyroid function in the modern combination antiretroviral therapy (cART) era are largely unknown. We aimed to investigate the prevalence and associated risk factors of thyroid dysfunction in well treated people living with HIV (PLWH) and matched uninfected controls and to examine whether HIV is independently associated with thyroid dysfunction. Design and Methods: Thyroid-stimulating hormone (TSH), free thyroxine, total thyroxine, and free triiodothyronine were measured in 826 PLWH from the Copenhagen co-morbidity in HIV infection (COCOMO) Study and in 2503 matched uninfected controls, and medical treatment for hypothyroidism or hyperthyroidism was recorded. Multinomial logistic regression adjusting for known risk factor was used to examine the association between HIV and thyroid dysfunction and multivariate linear regression to study the association between HIV and serum TSH concentrations. Results: The PLWH were generally well treated, with 95% having undetectable viral replication. Among PLWH and controls 31 (3.8%) and 114 (4.6%) had hypothyroidism, and 7 (0.8%) and 21 (0.8%) had hyperthyroidism, respectively. In adjusted analyses, we found no significant associations between HIV and hypothyroidism OR 0.8 [95% confidence interval (CI) 0.6–1.3], P  = 0.40 or between HIV and hyperthyroidism OR 1.1 (95% CI 0.5–2.5), P  = 0.91. Furthermore, serum TSH concentration was unrelated to HIV status ( P  = 0.6). Conclusion: There was no difference in the prevalence of hyperthyroidism or hypothyroidism in well treated PLWH compared with uninfected controls. HIV status was not associated with thyroid dysfunction or serum TSH concentration.